Control into conjunctive participle clauses : the case of Assamese - Haddad, Youssef A., 1972- (Trends in linguistics. Studies and monographs ;, 2011)
Control is a relation of co-identity between a pronounced subject (or object) in a matrix clause and a usually unpronounced subject in a subordinate, non-finite clause. The volume investigates Adjunct Control in Assamese, a South Asian language, within the framework of syntactic theory. While Forward Control is a cross-linguistically common control pattern, Assamese also allows three less common types of control structures: Backward, Copy, and Expletive Control. The volume documents all four types, analyzes them within the most recent framework of syntactic theory and delineates the theoretical implications.